CHANGES IN MORPHOMETRIC PARAMETERS OF CHILDREN AND ADOLESCENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The study studied the morphometric changes in body parts of 100 boys and 120 girls 10 years old with scoliosis and compared with healthy children (n=240, 100 boys and 140 girls). It was established that scoliosis leads to violations of not only the functions of the musculoskeletal system, but also the development of negative shifts in anthropometric parameters.